Metabolic diseases and interferon immune responses - Haiyan Zhou; Chunyan Liu; Yuerong Zhang; Hui Zheng (Interdisciplinary Medicine)
Abstract Metabolic diseases, including obesity, diabetes, and metabolic‐associated fatty liver disease (MAFLD), are increasingly common worldwide, posing a significant public health challenge. Recent research has revealed a complex interplay between these metabolic disorders and interferon (IFN) immune responses. As key immune regulators, interferons coordinate the host's defense against viral infections and are essential for maintaining immune homeostasis. However, metabolic dysregulation can significantly disrupt IFN signaling pathways, affecting the intensity and efficiency of immune responses. Conversely, alterations in IFN signaling can influence the onset and progression of metabolic diseases. This review explores the mechanisms by which metabolic diseases modulate IFN responses, focusing on how obesity, diabetes, and MAFLD alter IFN signaling. Additionally, we examine the implications of the changes in IFN immune responses for the progression of metabolic diseases. By synthesizing current research, this review aims to elucidate the interplay between IFN immune responses and common metabolic diseases, offering insights for future research and clinical applications in the field of IFN‐related metabolic diseases.